DNA EXTRACTION FROM LOCAL SOUVENIR OF SUKU ANAK DALAM JAMBI WITHOUT LIQUID NITROGEN USING CTAB METHOD - Wulandhari; Damayanti, Inggar; Bintoro, Afif; Hariri, Muhammad Rifqi (Jurnal Belantara, 2024)
One of the local souvenirs from Jambi is accessories made from the seed bark of the sebalik sumpah tree. The sebalik sumpah tree is currently quite rare. Through DNA isolation, sebalik sumpah is one of the efforts of genetic conservation and as a first step in cultivating sebalik sumpah trees. DNA isolation is the initial stage in molecular analysis. The purpose of DNA isolation is to obtain genomic DNA from a sample. Plant DNA isolation generally uses fresh plant samples, with young and soft plant parts. This is recommended to obtain good quality genomic DNA. However, with the limitations of fresh samples, a method is needed that is able to extract DNA from plants that have changed shape and have undergone processing. Each plant requires a different method to obtain DNA. The CTAB (Cethyl Trimethyl Ammonium Bromide) buffer method is a method commonly used in plants because it is able to extract DNA with high polysaccharide and phenol content, so many have modified the method. This study aims to determine the success of the CTAB method without nitrogen in extracting processed materials and the length of incubation time at the precipitation stage. Extraction was carried out by liquid nitrogenless CTAB method with the addition of PVP (Polyvinylpolypyrrolidone). The results show that the CTAB method without liquid nitrogen is able to extract plant samples that have undergone processing and the length of incubation time at the precipitation stage affects the DNA produced.